English for careers : business, professional, and technical. - Smith, Leila R., ....- (Upper Saddle River : Pearson, 2006)
KEY BENEFIT: Designed to keep pace with current workplace needs and the emerging 21st century culture, this book offers a lively, accessible, and user-friendly alternative for the many (including those with poor English skills) who dread the thought of barebones traditional grammar and communication instruction and its overkill of rules. KEY TOPICS: With a focus on real-world English skills that contribute to good workplace communication, this book emphasizes principles that reflect the oral and written communication of today's Standard English, as used by well-informed people. MARKET: For office managers, accountants, executives, office personnel department heads and sales people